Planar Cubic $G^1$ Hermite Interpolant with Minimal Quadratic Oscillation in Average (Communications in Mathematical Research, 2019)
In this paper we apply a new method to choose suitable free parameters of the planar cubic $G^1$ Hermite interpolant. The method provides the cubic $G^1$ Hermite interpolant with minimal quadratic oscillation in average. We can use the method to construct the optimal shape-preserving interpolant. Some numerical examples are presented to illustrate the effectiveness of the method.